TRADISI WALIMA SEBAGAI BASIS AKUNTABILITAS SPIRITUAL: INTERPRETASI NILAI-NILAI BUDAYA GORONTALO - Fitri Nurhayati M, Niswatin, Tri Handayani Amaliah (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This study aims to examine the Walima tradition as a form of spiritual accountability practice grounded in Gorontalo local wisdom through the paradigm of spiritualism. The research employs a qualitative approach using a literature review method of relevant scholarly publications from the period 2015–2024. Data analysis is conducted using thematic analysis to identify the core values embedded in the Walima tradition. The findings reveal that Walima embodies three main values: spiritual values, socio-cultural values, and spiritual accountability values. Spiritual values are reflected in practices of gratitude, almsgiving, sincerity, and devotion to the Prophet Muhammad (peace be upon him), which are manifested through voluntary community contributions. Socio-cultural values, particularly the concept of Huyula, emphasize the importance of togetherness, mutual cooperation, and trustworthiness as the foundation of social relations. Meanwhile, spiritual accountability in the Walima tradition is manifested through non-monetary, informal, and value-based forms of accountability, oriented toward vertical accountability to God and horizontal accountability to the community.This study concludes that the Walima tradition represents a form of spiritual accounting rooted in local wisdom that broadens the understanding of accountability beyond formal financial recording. These findings are expected to contribute theoretically to the development of spiritual accounting and culture-based accounting.